Yamabiko gakkō - Muchaku, Seikyō 1927- (Dokuritsu Puro meiga tokusen, 1997)
Dramatization of the life of Muchaku Seikyō and his experiences teaching in rural Yamagata prefecture that led to his compilation of the bestselling collection of children's writings, Yamabiko gakkō